A Case Report of Recurrent Pyogenic Granuloma with Satellitosis - Parajuli, Sudip; Das, Anil K; Paudel, Upama (Journal of Institute of Medicine Nepal, 2019)
Recurrent pyogenic granuloma with satellitosis is an uncommon condition with majority of cases resolving within one year after treatment. We report a case of recurrent pyogenic granuloma in a middle aged man who kept on relapsing at different point of time despite treatment with electrocoagulation, cryosurgery and oral methotrexate. The case highlights the unusual presentation of relatively common condition of pyogenic granuloma.